Expression of MxA in esophageal cancer cell lines can influence sensitivity to chemotherapeutic agents but this does not require apoptosis - R. M. Hayes; T. R. O'Donovan; S. L. McKenna (Cancer Medicine, 2024)
Abstract Esophageal cancer is a poor prognosis cancer characterized by intrinsic or acquired resistance to chemotherapeutic agents. The primary determinants of treatment failure are unknown. Expression of an anti‐viral protein, myxovirus resistance protein A (MxA) is de‐regulated in many cancers, including esophageal cancer, and its activity has been linked to apoptosis. This study has assessed whether MxA expression can influence the response of esophageal cancer cells to the chemotherapeutic agents 5‐fluorouracil (5‐FU) or oxaliplatin. MxA protein was differentially expressed in a panel of five esophageal cancer cell lines. KYSE450 and KYSE140 cells did not express MxA and were apoptosis incompetent. FLO‐1, KYSE270, and OE21 cells expressed MxA, were more drug‐sensitive and were apoptosis competent. MxA was artificially overexpressed in cell lines with no endogenous expression (KYSE450 and KYSE140). This increased the resistance of KYSE450 but not KYSE140 cells. Both cell lines remained apoptosis incompetent. We then evaluated siRNA knockdown of MxA in FLO‐1 cells and CRISPR knockout in OE21 cells. Knockdown of MxA significantly increased drug sensitivity and caspase‐3 activation in FLO‐1 cells. OE21‐MX1KO cells were also more drug‐sensitive, but in contrast to FLO‐1 cells, caspase‐3 activation was reduced. Collectively these data indicate that MxA can promote resistance to chemotherapy, but this does not always correspond with effects on apoptosis. Effects on apoptosis are cell line specific, suggesting that other co‐operating pathways determine the overall impact of MxA. Importantly, in cancer cells that overexpress the protein, drug sensitivity can be improved by interfering with MxA.